Strut and tie model optimization for reinforced concrete deep beam using genetic algorithm - Bambang Piscesa, PhD; Tavio Tavio (Journal of Civil Engineering, 2020)
This paper presents strut and tie model structural optimization of reinforced concrete deep beam using genetic algorithm. Genetic algorithm is used as the optimization platform as it does not require differentiation of the exact mathematical formulation to get the optimum solution. The force analysis is carried out using two-dimensional linear finite element method with truss element. The struts and ties design are based on ACI 318. One RC deep beam example is presented as an example. During optimization, there are two constraints which consisted of strength of the member alone and combination with deformation limit of the nodes. The stress ratio for both struts and ties are set to not exceed unity while the deformation was limited to 2.0 mm. From the optimization analysis, it can be concluded that genetic algorithm can be used to get the most optimum structural configuration which yield the most economical solution for design purposes. On the other hand, it is found out that optimizing only the strength alone can yield a more economical solution compared to the design references. However, if deformation constraint is added in the optimization parameters, larger deep beam depth is required to satisfy the deformation limits.